Crianças com baixa visão em uma brinquedoteca: o perceber na ludicidade - Moreira, Vânia Warwar Archanjo (2018)
The following research highlights the attempt of low-sight children's immersed in a toy-library ludic context, involved by playing practices. Established that embryonic academic ground our investigation aims to reach the general objective of peering the perception of low-sight children in a toy-library; additionally, it reaches to register and to reflect concerning both the perceptual vias they use in this recreative environment and the ludic possibilities offered to them in the light of the perception when they are in contact with this location. The theoretical foundation supports the visual impairment universe, especially about low sight, highlighting Masini (2007), Dall'Acqua (2002), Natalie Barraga (1977,1980,1985), Gasparetto and Nobre (2007), Amiralian (2004) and Ormelezi (2010); the debate about Merleau- Ponty's (2004, 2011, 2015) perception, together with the contributions of Masini (2003, 2007, 2012), Caminha (2013), Matthews (2011) and Coelho Jr and Carmo (1991); and the playfulness enlarging the toy-library as a propitious space for this dimensioning of the studied children, having as references Kishimoto (1994,2008), Rau (2011), Brougère (2004,2015), Wajskop (2007) and Gimenes and Teixeira (2011) in this discussion. Of a qualitative type, this study searched, at the Toy-library from "Brazilian Association for Assistance to Visual Impaired People" (Laramara), composing features to reach the proposed objectives, bringing concreteness to this investigation composed by observation, recording and later analysis of eight low-vision children, in the age group of around four years old, all of them with color perception and acuity. The surveyed data have revealed that the practice of playing at the toy-library is essential for the development of children with low vision, once are explored their perceptual feelings, which they dispose in the attempt to exhibit what is around them, with their own bodies in contact with this universe. Yet, the validation of ludic alternatives offered to this public enlightened by the perception when in contact with this environment has meant the projection of more well drafted ways and, therefore, indirect, for their interaction with the surrounding environment.